Γ-Fe2O3/CNTs Composites for Electrochemical Detection of Paracetamol: Synthesis, Phase Transition and Enhanced Properties. Issue 5 (18th May 2021) - Cai, Xin-Qin; Zhu, Kai; Liu, Bo-Tao; Zhang, Qing-Yu; Luo, Yu-Hui; Zhang, Dong-En
Abstract : In this work, γ -Fe2 O3 /CNTs composite was facile synthesized by simple hydrothermal method and hydrazine hydrate treatment at low temperature (CNTs = carbon nanotubes). The result of VSM shows that the saturation magnetization of Fe2 O3 /CNTs composites increase from 0 to 1.29 emu g −1 after hydrazine hydrate treatment, indicating that the Fe2 O3 in the composite transforms from α phase to γ phase. Moreover, the electrochemical properties of both α -Fe2 O3 /CNTs and γ -Fe2 O3 /CNTs was studied. Compared with α -Fe2 O3 /CNTs, γ -Fe2 O3 /CNTs shows enhanced electrochemical performance toward paracetamol determination. Under optimum condition, the γ -Fe2 O3 /CNTs modified electrode exhibits two linear ranges of 2.5 μ M−385 μ M and 593 μ M−1550 μ M and a low detection limit of 0.046 μ M. In addition, the constructed sensor can be successfully utilized for detecting paracetamol in different water bodies. This work provides a new clue for the design and construction of excellent electrochemical sensor for paracetamol determination.